On the visibility of airborne volcanic ash and mineral dust from the pilot’s perspective in flight - Weinzierl, Bernadett; Sauer, Daniel; Minikin, Andreas; Reitebuch, Oliver; Dahlkötter, Florian; Mayer, Bernhard; Emde, Claudia; Tegen, Ina; Gasteiger, Josef; Petzold, Andreas; Veira, Andreas; Kueppers, Ulrich; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2012)
In April 2010, volcanic ash from the Eyjafjalla volcano in Iceland strongly impacted aviation in Europe. In order to prevent a similar scenario in the future, a threshold value for safe aviation based on actual mass concentrations was introduced (2 mg m3 in Germany). This study contrasts microphysical and optical properties of volcanic ash and mineral dust and assesses the detectability of potentially dangerous ash layers (mass concentration larger than 2 mg m3) from a pilot’s perspective during a flight. Also the possibility to distinguish between volcanic ash and other aerosols is investigated. The visual detectability of airborne volcanic ash is addressed based on idealized radiative transfer simulations and on airborne observations with the DLR Falcon gathered during the Eyjafjalla volcanic ash research flights in 2010 and during the Saharan Mineral Dust Experiments in 2006 and 2008. Mineral dust and volcanic ash aerosol both show an enhanced coarse mode (>1 lm) aerosol concentration, but volcanic ash aerosol additionally contains a significant number of Aitken mode particles (<150 nm) not present in mineral dust. Under daylight clear-sky conditions and depending on the viewing geometry, volcanic ash is visible already at mass concentrations far below what is currently considered dangerous for aircraft engines. However, it is not possible to visually distinguish volcanic ash from other aerosol layers or to determine whether a volcanic ash layer is potentially dangerous (mass concentration larger or smaller than 2mgm3). Different appearances due to microphysical differences of both aerosol types are not detectable by the human eye. Nonetheless, as ash concentrations can vary significantly over distances travelled by an airplane within seconds, this visual threat evaluation may contribute greatly to the short-term response of pilots in ash-contaminated air space.